2019
DOI: 10.23960/jpf.v9.n2.202111
|View full text |Cite
|
Sign up to set email alerts
|

Student Practicum Competencies through Lesson Study with the application of Argument Driven Inquiry

Abstract: This study intends to analyse the student's practicum competencies through Lesson Study activities by applying the Argument Driven Inquiry learning model which was studied using qualitative research with descriptive qualitative analysis techniques. The sample is 13 students in the fourth semester of physics education. Based on students’ practicum reports, the percentage of learning outcomes in the first Lesson Study was 70.91, the second Lesson Study was 84.83. The indicators of student practicum competencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
(8 reference statements)
0
0
0
Order By: Relevance
“…The average learning outcomes in cycle I reached 75 and increased in cycle II to 85. Likewise, ADI learning using lesson study concluded that the learning provided was effective for improving learning outcomes (Delfakhria & Solfema, 2022;Siregar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The average learning outcomes in cycle I reached 75 and increased in cycle II to 85. Likewise, ADI learning using lesson study concluded that the learning provided was effective for improving learning outcomes (Delfakhria & Solfema, 2022;Siregar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristics of lesson study learning are starting from the process of planning, observing, reflecting, discussing and even revising learning and re-implementing. So that lesson study is part of improving pedagogical quality and evaluating learning outcomes through student activeness (Ratnawati, 2019;Siregar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation